A survey of pediatric dentists' caries-related treatment decisions and restorative modalities - A web-based survey - Hassan S. Halawany; Fouad Salama; Vimal Jacob; Nimmi Biju Abraham; Tarfa Nasser Bin Moharib; Abdulfatah Samih Alazmah; Jawaher Abdulaziz Al Harbi (Elsevier, 2017)
Objective: To identify current practices and the preferred caries-related treatment decisions and restorative modalities of primary teeth among pediatric dental practitioners in Saudi Arabia. Materials and methods: This was a web-based cross-sectional survey conducted among licensed pediatric dental practitioners in Saudi Arabia. Following the retrieval of the email addresses from the Saudi Dental Council, an email explaining the purpose of the study and a link to SurveyMonkey electronic survey consisting of 23 questions was sent to all the members registered under the pediatric dentistry practitioners, starting in September till December 2013. The data obtained was analyzed using descriptive statistics and chi square with and without tabulation processes. The level of significance was set at p < 0.05. Results: A total of 108 [54 (50%) male and 54 (50%) female] pediatric dental practitioners responded to the survey out of 308 targeted individuals for an overall response rate of 35.1%. About 65% of the respondents reported that they have never considered pre-veneered or Zirconia crowns as a restorative option for carious vital anterior primary teeth. About 40% reported doing pulpectomy and restored with composite strip crowns at all times. About 86% of the respondents reported doing pulpotomy and stainless steel crown for restoring carious vital posterior primary teeth whereas 73.8% reported restoring with composite resin. However, 83.1% of the respondents reported that they never used pre-veneered or Zirconia crowns after pulpotomy for restoring carious vital posterior primary teeth. A significantly higher number of male participants reported that they used esthetic pediatric crowns in their practice compared to female participants (p < 0.001). Conclusion: The prevalence of use of composite resin to restore primary teeth was higher compared to glass ionomer cements and amalgam whereas a limited use of esthetic pediatric crowns was found among the sample surveyed. Esthetic pediatric crowns were more utilized by male compared to female participants. Keywords: Pediatric dentists, Primary teeth, Restorative materials, Composite resin